1998
DOI: 10.3354/dao033151
|View full text |Cite
|
Sign up to set email alerts
|

Modes of transmission of Loma salmonae (Microsporidia)

Abstract: Loma salmonae (Putz, Hoffman and Dunbar, 1965) Morrison and Sprague, 1981 (Microsporidia) causes prominent gill disease in pen-reared chinook salmon Oncorhynchus tshawytscha in the Pacific Northwest. Transmission of the parasite was examined by exposing Pacific salmon Oncorhynchus spp. to infectious spores by various routes: per OS, intraperitoneal, intramuscular, and intravascular injection, by cohabitation with infected fish, and by placement of spores directly on the gill. All exposure methods led to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…Successful experimental infections have been performed by the addition of spores to tanks containing suitable host fish, the feeding of infected tissues, cohabitation of naive with infected fish, and intra-peritonea1 and intramuscular injections (for review see Lom & Dykova 1992, Shaw et al 1998). However, on several different occasions Egusa (unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Successful experimental infections have been performed by the addition of spores to tanks containing suitable host fish, the feeding of infected tissues, cohabitation of naive with infected fish, and intra-peritonea1 and intramuscular injections (for review see Lom & Dykova 1992, Shaw et al 1998). However, on several different occasions Egusa (unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Hosts were tested as outlined in Table 1 following the protocol of Kent et al (1995) and Shaw et al (1998). Test fish (n = 20) of each species were placed in a tank (fresh or seawater dependent on fish species) with 10 positive control chinook salmon and were not fed for 2 d prior to exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Fish were fed macerated gill tissue infected with Loma salmonae over 3 d. During feeding water flow was turned off for 2 h to facilitate ingestion of gill tissue. On the fourth day 10 experimental fish and 5 controls were removed and infected per OS using a syringe containing a gill slurry (see Shaw et al 1998); their fins were clipped, and the fish were placed back in the tank. All fish were examined 56 d later by wet mount and histology for L. salmonae, a time that we have previousiy determined is optimum for the detection of experimental infections .…”
Section: Methodsmentioning
confidence: 99%
“…Hauck (1984) suggested infection might occur by direct uptake of spores by phagocytic cells within the gills. However, placement of infectious spores directly on gills of Chinook did not result in infection Shaw et al (1998) found spores and possible sporoplasms in the intestinal epithelium shortly after exposure by standard histology. Sánchez et al (2001a) further confirmed this observation and found the parasite in epithelial cells and the lamina propria of the small intestine as early as 12 h post-exposure (p.e.)…”
Section: Sequential Developmentmentioning
confidence: 99%
“…We have also found that free spores within the kidney interstitium persist for many months after xenomas have resolved ). Shaw et al (1998) showed that fish could also be infected by co-habitation, anal gavage, and intramuscular, intraperitoneal and intravascular injection of spores. The onset of xenoma formation and clearance of xenomas is delayed in fish infected by natural co-habitation compared to per os infection .…”
Section: Recoverymentioning
confidence: 99%